Microbial community response to cover cropping varied with time after termination - Anuoluwapo Ogunleye; Vesh R. Thapa; Deb R. Aryal; Rajan Ghimire; Veronica Acosta‐Martinez (Agricultural & Environmental Letters, 2023)
Abstract This study evaluates cover crop (CC) effects on microbial community structure in a winter wheat–sorghum–fallow rotation with pea, oat, and canola; mixtures of pea and oat; pea and canola; pea, oat, and canola; and six species mixture (SSM) of pea, oat, canola, hairy vetch, forage radish, and barley as CCs, and fallow as treatments. Soil microbial community structure was analyzed at CC termination (phase I), 36 days (phase II), and a year (phase III) after termination using an ester‐linked fatty acid methyl ester analysis. Total microbial biomass (TMB) under oats was significantly greater than under canola (by 47%) in phase I (p ≤ 0.05). The TMB was >48% under pea, pea + canola, and SSM, and arbuscular mycorrhizal fungi was 70%–93% more under pea, canola, and their mixtures than fallow in phase II. While microbial abundance varied with CCs at and after 36 days post‐termination, these effects did not persist for a year. Long fallow period after cropping or cover cropping appears detrimental to microbial community proliferation.